From awareness to adoption: English teachers’ artificial intelligence acceptance in junior high schools - Faisal Faisal; Nirma Oktaviana Harningsih; Razlina Razali (English Learning Innovation, 2026)
This study investigates the level of artificial intelligence acceptance (AIA) among 35 English teachers from junior high schools in a regency in Central Java Indonesia. Using a descriptive quantitative design, data were collected through a closed-ended questionnaire, which measured six indicators: perceived usefulness, perceived ease of use, self-efficacy, anxiety, attitude toward use, and behavioral intention. The results revealed a high overall level of AIA, with a mean score of 3.86. The highest mean scores were observed in perceived usefulness, perceived ease of use, attitude toward use, and behavioral intention, suggesting that teachers recognize the relevance and benefits of artificial intelligence in supporting instructional activities. Conversely, self-efficacy and anxiety were at moderate levels, indicating a critical gap: while teachers accept AI, they still experience limited confidence and psychological barriers to independent adoption. This study contributes to the field by providing a baseline descriptive analysis of the readiness of in-service English teachers. It confirms the centrality of perceived usefulness but also underscores that self-efficacy and anxiety function as critical limiting factors in implementation readiness. The findings highlight the need for targeted professional development and institutional support that emphasizes hands-on training to strengthen competence and reduce anxiety.